Napotitve ostajajo izziv za zakonodajalca in nadzorne organe - Mišič, Luka (Pravnik, 2026)
On 13 April 2026, the Society for Labour Law and Social Security held a professional consultation at the Faculty of Law of the University of Ljubljana on the challenges of cross-border provision of services and the posting of workers. Slovenia is one of the leading countries in terms of the number of posted workers. While posted workers contribute to the competitiveness of the European Union’s common market, the posting of workers also gives rise to political friction and creates scope for unlawful practices and violations of workers’ rights. The discussion highlighted the complexity of the legal regulation of postings, which encompasses not only labour law and social security law, but also tax and migration law. Numerous practical challenges were discussed, including subsidiary liability in the construction sector, the obtaining of A1 certificates, abuses relating to so-called simultaneous employment, and the challenges faced by self-employed persons in relation to postings. Participants pointed to inconsistent practice among EU Member States and to the insufficient protection of workers, especially third-country nationals, with Slovenia often serving as an entry point for work in other countries. Some widespread unfair practices, such as irregular payments and poor living conditions, were highlighted as being difficult for supervisory authorities to detect. It was also noted that some unfair practices may be committed by supervisory authorities in host Member States themselves. Nevertheless, postings remain important for the functioning of the EU single market and, in light of this, the panellists adopted several recommendations.
Keywords: coordination of social security systems; cross-border provision of services; čezmejno izvajanje storitev; davčno pravo; delovno pravo; koordinacija sistemov socialne varnosti; labour law; napotitve; postings; pravo socialne varnosti; simultaneous employment; social security law; sočasne zaposlitve; tax law